The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1128/aem.63.11.4171-4177.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated dissolved CO2 levels on batch and continuous cultures of Aspergillus niger A60: an evaluation of experimental methods

Abstract: The effects of elevated levels of dissolved carbon dioxide (dCO2), produced by gassing with CO2-enriched gas mixtures, upon an industrial strain of Aspergillus niger (strain A60) producing citrate and gluconate were quantitatively assessed. Particular attention was paid to the reliability and accuracy of the steam-sterilizable dCO2 probe, especially in the presence of high concentrations of potentially interfering acidic species. The response of the organism to elevated dCO2 levels was assessed by using both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
(49 reference statements)
2
6
0
Order By: Relevance
“…stat cultivation allows for a better physiological adaptation to excess CO 2 than the dynamic conditions of fedbatch cultivation. A similar phenomenon has been observed in Aspergillus [60].…”
Section: Physiological Responses To Cosupporting
confidence: 85%
“…stat cultivation allows for a better physiological adaptation to excess CO 2 than the dynamic conditions of fedbatch cultivation. A similar phenomenon has been observed in Aspergillus [60].…”
Section: Physiological Responses To Cosupporting
confidence: 85%
“…Carbon dioxide (CO 2 ) produced from cell metabolism may accumulate to high concentrations during high cell density cultures, particularly under the elevated hydrostatic pressures typical of industrial scale fermenters. High dissolved carbon dioxide (dCO 2 ) levels usually occur at the end of periods of rapid growth or in high cell concentration cultures (McIntyre and McNeil, 1997). High dCO 2 or high carbon dioxide partial pressures (pCO 2 ) can cause inhibitory effects on growth and metabolism of most industrially important microorganisms (Bäumchen et al, 2007;Castan et al, 2002;Dixon and Kell, 1989;El-Sabbagh et al, 2006;Jones and Greenfield, 1982;McIntyre and McNeil, 1997;Mori et al, 1983;Seáñez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Only in some cases pCO 2 has been measured in the exhaust gas. This is important since there exists a complex relationship between dCO 2 and CO 2 in the gas phase that cannot be easily predicted, as both variables can constantly vary in a culture due to changes in specific and overall oxygen uptake rate, as well as operational changes in gas flow rate, agitation rate, and total pressure, among others (Dahod 1993;El-Sabbagh et al, 2006;McIntyre and McNeil, 1997). To overcome the limitations of studies reported to date, in the present work the effect of CO 2 was determined in batch cultures of recombinant E. coli by continuously measuring dCO 2 online and controlling it at constant values.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the more interesting findings, researchers have shown that opening the shake flask closure for sampling allows diffusion of gases into the atmosphere, such that CO 2 concentrations decrease temporarily in the broth as well as in the headspace, thereby significantly impacting the community structure of soil microbes (Takahashi & Aoyagi, ). A study conducted by McIntyre and McNeil () concluded that culture is more vulnerable to CO 2 inhibition in the lag phase. In addition, during the inoculation step, the culture can experience many pressures due to the significant differences in the environment of a shake flask and in the bioreactor conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, phosphofructokinase, which is a rate‐limiting enzyme in the glycolytic pathway, is inhibited by low intracellular pH. Thus, dCO 2 has a direct impact on metabolic pathways (McIntyre & McNeil, ).…”
Section: Introductionmentioning
confidence: 99%